Gender, Intersections, and Institutions : Intersectional Groups Building Alliances and Gaining Voice in Germany - Davidson-Schmich, Louise K., 1968-; Project Muse. (Ann Arbor : University of Michigan Press, 2017)
Germany serves as a case study of when and how members of intersectional groups-individuals belonging to two or more disadvantaged social categories-capture the attention of policymakers, and what happens when they do. This edited volume identifies three venues through which intersectional groups are able to form alliances and generate policy discussions of their concerns. Original empirical case studies focus on a wide range of timely subjects, including the intersexed, gender and disability rights, lesbian parenting, women working in STEM fields, workers' rights in feminized sectors, women in combat, and Muslim women and girls.
5. Gendering the Controversy over Education Policy Reform in Hamburg, Germany -- Jeff Bale6. Gendering the German Minimum Wage Debate: A Male Frame for a Female Problem -- Annette Henninger -- 7. Amending Germany's Life Partnership Law: Emerging Attention to Lesbians' Concerns -- Louise K. Davidson-Schmich -- 8. Grassroots Organizing in Eastern Germany to Promote Women in STEM -- Katja M. Guenther -- Conclusion: Power, Institutions, and Intersectional Research in Germany and Beyond -- Louise K. Davidson-Schmich.
Description based on print version record.
Keywords: Pressure groups; Politics and government; Minorities -- Political activity; Minorities -- Civil rights; SOCIAL SCIENCE -- Gay Studies; Intersectionnalite -- Aspect politique -- Allemagne; Groupes de pression -- Allemagne; Minorites -- Droits -- Allemagne; Minorites -- Activite politique -- Allemagne; Intersectionality (Sociology) -- Political aspects -- Germany; Pressure groups -- Germany; Minorities -- Civil rights -- Germany; Minorities -- Political activity -- Germany; Germany; Germany -- Politics and government -- 1990-; Electronic books